Challenges and prospects of adopting climate-smart agricultural practices and technologies: Implications for food security - Rusha Begna Wakweya (Journal of Agriculture and Food Research, 2023)
Climate-smart agriculture (CSA) has become popular as a practical solution for food insecurity in the face of climate change. This paper aims to review the challenges and prospects of adopting climate-smart agricultural practices and technologies and their implications for food security in sub-Saharan Africa. The study used an integrative literature review based on inclusion and exclusion criteria. The result of the review indicated that lack of appropriate policies and political commitment, lack of knowledge of CSA technologies by smallholder farmers, institutional constraints, and financial constraints were identified as the main challenges to the adoption of CSA technologies and practices, while the availability of resources in the form of projects, programs, technologies, practices, and other applications were opportunities for policymakers, advisors, and farmers. Therefore, there is a need for the linkage of farmers, researchers, and extension practitioners, considering appropriate sets of CSA interventions of relevant scale, selected and tailored to local specific contexts and livelihood needs.